Alcohol consumption patterns and attitudes toward drink-drive behaviours and road safety enforcement strategies. (January 2017) - Stephens, A.N.; Bishop, C.A.; Liu, S.; Fitzharris, M.
Highlights: Alcohol consumption patterns and attitudes towards drink-driving were examined in a large sample of drivers (N = 2994). Drivers with more risky alcohol consumption patterns were more likely to drink and drive when they could get away with it. Drivers with more risky alcohol consumption patterns were less likely to perceive the crash risk associated with drink-driving. Drivers who reported drink-driving were also more likely to have friends and family who frequently engage in the behaviour. Abstract: Background: Alcohol contributes to approximately 30% of all serious crashes. While the majority of drivers acknowledge the risks associated with drink-driving, a significant proportion of the population continue to engage in this behaviour. Attitudes towards drink-driving as well as personal alcohol consumption patterns are likely to underpin a driver's decision to drink-drive. These associations were explored in the current study. Methods: A large (N = 2994) cross-sectional online survey of a representative sample of drivers in Australia was conducted. Participants provided information about their own alcohol consumption patterns, drink-driving behaviour as well as attitudes towards drink-driving (own and others) and enforcement strategies. Results: Alcohol consumption patterns differed according to age, gender and work status. Drivers who reported drink-driving behaviour and had high risk alcohol consumption patterns were less likely to agree that drink-driving leads to increased crash risk and more likely to agree they drink and drive when they believed they could get away with it. In contrast, drivers who did not report drink-driving and had low risk consumption patterns were more likely to report that the enforcement strategies are too lenient. Binary logistic regression showed that high risk alcohol consumption patterns and agreement from drivers that they drink and drive when they believe they can get away with it had the strongest associations with drink-driving. These findings highlight the relationships between one's drinking patterns, drink-drive behaviour and attitudes towards drink-driving and drink-driving enforcement Conclusions and implications: The patterns of associations that emerged suggest that drink-driving is the expression of a broader health issue for the most "at-risk" cohort of drinkers. The decision to drink and drive may result from a need borne from an alcohol dependent lifestyle exacerbated by a social acceptability of the behaviour and positive attitudes towards one's ability to drink-drive with few adverse consequences. Therefore, the broader alcohol consumption patterns of drink-drivers needs to be considered when targeting drink-drive reductions.